Wiley GAAP for Governments 2014 : Interpretation and Application of Generally Accepted Accounting Principles for State and Local Governments - Ruppel, Warren (Hoboken : Wiley, 2014)
The most practical, authoritative guide to governmental GAAP Wiley GAAP for Governments 2014 is a comprehensive guide to the accounting and financial reporting principles used by state and local governments as well as other governmental entities. Designed with the needs of the user in mind, this comprehensive resource presents the important developments in governmental GAAP during the past year. Full coverage of authoritative accounting standardsExtremely useful and user-friendly examples, illustrations, and helpful practice hintsA comprehensive gui.
New Developments -- Foundations of Governmental Accounting -- Fund Accounting Fundamentals -- General Fund and Special Revenue Funds -- Capital Projects Funds -- Debt Service Funds -- Proprietary Funds -- Fiduciary Funds -- Financial Statements Prepared by Governments -- The Importance of Budgets to Governments -- Definition of the Reporting Entity -- Cash and Investments-Valuation and Disclosures -- Derivative Instruments -- Capital Assets -- Debt and Other Obligations -- Landfill Closure and Postclosure Care Costs -- Postemployment Benefits-Pension and Other -- Compensated Absences -- Accounting for Leases -- Nonexchange Transactions -- Risk Financing and Insurance-Related Activities/Public Entity Risk Pools -- Pension and OPEB Plan Financial Statements -- Educational and Other Governmental Entities -- Appendix: Disclosure Checklist.
Includes index.
Print version record.
Keywords: Finance, Public -- Accounting -- Standards -- United States; Local finance -- Accounting -- Standards -- United States; Accounting -- Standards -- United States; Accounting -- Standards -- United States; Finance, Public -- Accounting -- Standards -- United States; Local finance -- Accounting -- Standards -- United States; BUSINESS & ECONOMICS -- Industries -- General; Accounting -- Standards; Finance, Public -- Accounting -- Standards; Local finance -- Accounting -- Standards; United States; Electronic books